Prospective evaluation of malignant cell seeding after percutaneous endoscopic gastrostomy in patients with oropharyngeal/esophageal cancers - Ellrichmann, M.; Sergeev, P.; Bethge, J.; Arlt, A.; Topalidis, T.; Ambrosch, P.; Wiltfang, J.; Fritscher-Ravens, A. (Endoscopy, 2013)
Background and study aims: Insertion of a percutaneous endoscopic gastrostomy (PEG) is standard care for many patients with oropharyngeal (ENT) and esophageal malignancies in order to ensure enteral feeding. The current pull-through insertion technique involves direct contact with the tumor and case reports have demonstrated the presence of metastases at insertion sites. The aim of the current study was to prospectively evaluate the risk of malignant cell seeding and the development of abdominal wall metastases after PEG placement.Patients and methods: A total of 50 consecutive patients with ENT/esophageal tumors were included. After PEG placement (40 pull-through technique, 10 direct insertion), brush cytology was taken from the PEG tubing and the transcutaneous incision site. A second cytological assessment was performed after a follow-up period of 3 – 6 months.Results: In total, 26 patients with ENT cancer, 13 with esophageal cancer, and one with esophageal infiltration of lung cancer underwent pull-through PEG placement with no immediate complications. Cytology following brushing of tubing and incision sites demonstrated malignant cells in 9 /40 cases (22.5 %). Correlation analyses revealed a higher rate of malignant seeding in older patients and in those with higher tumor stages. At follow-up, cytology was undertaken in 32 /40 patients who had undergone pull-through PEG placement. Malignant cells were present in three on cytology, resulting in a metastatic seeding rate of 9.4 %. Conclusion: This study showed that malignant cells were present in 22.5 % of patients immediately after pull-through PEG placement; local metastases were verified at follow-up in 9.4 %, all of which were from esophageal squamous cell carcinoma. This risk is particularly high in the older age group and in patients with higher tumor stages. Therefore, pull-through PEG placement should be avoided in these patients and direct access PEG favored instead.